Citizenship Education to Strengthen Student Character - Baidi Baidi; Hibana Hibana; Susilo Surahman (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2021)
Since the era of President Sukarno, citizenship education has been taught precisely from around 1901 to 1970, but in the learning process, students still find some obstacles. This study aims to determine the implementation of citizenship education learning in strengthening students' characterâ€”qualitative field research method with a descriptive approach. The research was conducted at Integrated Islamic Primary School Salsabila Banguntapan Yogyakarta.Â Data collection techniques through observation, interview and documentation. The validity of the data is obtained by triangulation. Data analysis techniques using Miles and Huberman's theory are with stages of data reduction, display and conclusion drawing. The research results are 1) education learning planning is made in the syllabus and character education learning plan. 2) In the learning process, the teacher applies and uses various methods and learning resources and integrates them into characterful activities. 3) evaluation is done by the teacher through assessment, although not optimal.